Reading and Print Cultures in Waterford, 1865–1939. Issue 1 (December 2022) - Toms, David
This article sets out to explore the emergence of reading and print cultures in Waterford over the period from the opening of the city's Free Public Library to the outbreak of the Second World War in the twentieth century. It is intended to add to the growing body of writing emerging on reading and books in Ireland by honing in on the development of a local reading culture in an era of more democratic access to books, periodicals and other printed matter. By surveying the development of various lending and circulation libraries up to the establishment of the Waterford Free Public Library in 1896 and beyond into the Free State era, the argument will be made that many of the concerns around self-improvement and literacy remained constant despite the shift from member-run libraries to municipal libraries and from Victorian concerns about moral self-improvement to early Irish state concerns about nation-building and Catholic morality in the 1920s and 1930s. The article will also explore the publishing and book trade in the city throughout the same period. This small but significant industry provided employment for some of the very people who were the target of self-improvement and concerns about their ability to consume 'morally dubious' literature.